2009
DOI: 10.1016/j.jbiomech.2009.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of footwear on foot motion during walking and running

Abstract: There are evidences to suggest that wearing footwear constrains the natural barefoot motion during locomotion. Unlike prior studies that deduced foot motions from shoe sole displacement parameters, the aim of this study was to examine the effect of footwear motion on forefoot to rearfoot relative motion during walking and running. The use of a multi-segment foot model allowed accurate both shoe sole and foot motions (barefoot and shod) to be quantified. Two pairs of identical sandals with different midsole har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
70
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 27 publications
11
70
0
5
Order By: Relevance
“…In line with Morio et al(2009) our results show that the rapid eversion motion occurred faster for shod locomotion compared to barefoot.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with Morio et al(2009) our results show that the rapid eversion motion occurred faster for shod locomotion compared to barefoot.…”
Section: Discussionsupporting
confidence: 93%
“…Previous biomechanical studies investigated the implications of walking in flip‐flops compared to barefoot and/or closed toe footwear (Chard, Greene, Hunt, Vanwanseele, & Smith, 2013; Morio et al, 2009; Shroyer & Weimar, 2010; Zhang et al, 2013) further support the hypothesis that all shoes, even the open‐toe footwear, yield different ankle kinematics compared to the barefoot condition. In line with Morio et al(2009) our results show that the rapid eversion motion occurred faster for shod locomotion compared to barefoot.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Footwear has a great influence on natural foot condition [16]. There is more eversion of forefoot in barefoot locomotion, and more inversion while shod [17]. It is important to discuss the differences women, and suggested that women Leather and Footwear Journal 16 (2016) 1 diferenþele între mersul cu picioarele goale ºi cel cu pantofi, având în vedere cã piciorul se aflã în stare naturalã atunci când este desculþ.…”
Section: Introductionunclassified
“…Încãlþãmintea influenþeazã semnificativ starea naturalã a piciorului [16]. Antepiciorul prezintã o eversie mai mare în timpul mersului desculþ ºi o inversie mai mare în timpul mersului cu pantofi [17]. Este important sã se discute 30…”
unclassified